GREEN HRM, EMPLOYEE GREEN BEHAVIOR, DAN ENVIRONMENTAL PERFORMANCE DALAM PENGUATAN KINERJA LINGKUNGAN ORGANISASI: SEBUAH LITERATURE REVIEW - Elly Rahayu; Wan Mariatul Kifti; Donni Nasution; Feriyanto; Jufrizen (Smart Education, 2026)
Abstract: The growing awareness of the importance of sustainability has prompted organizations to incorporate environmental elements into management and operational procedures. Green Human Resource Management (GHRM) is one of the most studied approaches. It is considered to be able to encourage the formation of Employee Green Behavior (EGB) and improve the company's Environmental Performance (EP). The purpose of this study is to analyze and synthesize previous research on green human resource management, green employee behavior, and environmental achievement. This study uses a qualitative literature review method. Data was obtained from 30 journal articles published from 2020–2026. This article consists of 10 articles on Green Human Resource Management, 10 articles on Green Worker Behavior, and 10 articles on Environmental Performance. The selection of articles is based on the relevance of the topic, the year of publication, and the number of citations. Content analysis and theme synthesis are used to find patterns of relationships between variables, research trends, and research gaps that need to be improved. The results of the study show that GHRM plays an important role in creating environmentally friendly worker behavior. Through various practices such as green labor acceptance, green training, and green performance assessments, GHRM plays this role. Through resource use efficiency, waste reduction, and increased environmental awareness, EGB has been shown to improve environmental performance. In addition, it was found that the research conducted was still mainly on the manufacturing and hospitality industries, while the amount of research conducted in the field of education and developing countries was very limited. According to this study, GHRM, EGB, and EP are important components in supporting the sustainable strengthening of organizational environmental performance. Keywords: Green Human Resource Management; Employee Green Behavior; Environmental Performance; Sustainability; Literature Review. Abstrak: Bertambahnya kesadaran akan pentingnya keberlanjutan telah mendorong organisasi untuk memasukkan elemen lingkungan ke dalam prosedur manajemen dan operasional. Green Human Resource Management (GHRM) adalah salah satu pendekatan yang banyak dipelajari. Dianggap dapat mendorong pembentukan Employee Green Behavior (EGB) dan peningkatan Environmental Performance (EP) perusahaan. Tujuan dari penelitian ini adalah untuk menganalisis dan mensintesis penelitian sebelumnya tentang manajemen sumber daya manusia hijau, perilaku karyawan hijau, dan prestasi lingkungan. Penelitian ini menggunakan metode review literatur kualitatif. Data diperoleh dari 30 artikel jurnal yang dipublikasikan dari tahun 2020–2026. Artikel ini terdiri dari 10 artikel Manajemen Sumber Daya Manusia Hijau, 10 artikel Perilaku Pekerja Hijau, dan 10 artikel Kinerja Lingkungan. Pemilihan artikel didasarkan pada relevansi topik, tahun publikasi, dan jumlah sitasi. Analisis isi dan sintesis tema digunakan untuk menemukan pola hubungan antarvariabel, tren penelitian, dan kesenjangan penelitian yang perlu diperbaiki. Hasil penelitian menunjukkan bahwa GHRM memainkan peran penting dalam menciptakan perilaku pekerja yang ramah lingkungan. Melalui berbagai praktik seperti penerimaan tenaga kerja hijau, pelatihan hijau, dan penilaian kinerja hijau, GHRM memainkan peran ini. Melalui efisiensi penggunaan sumber daya, pengurangan limbah, dan peningkatan kesadaran lingkungan, EGB telah terbukti meningkatkan kinerja lingkungan. Selain itu, ditemukan bahwa penelitian yang dilakukan masih terutama pada industri manufaktur dan perhotelan, sementara jumlah penelitian yang dilakukan pada bidang pendidikan dan negara berkembang sangat terbatas. Menurut penelitian ini, GHRM, EGB, dan EP merupakan komponen penting dalam mendukung penguatan kinerja lingkungan organisasi secara berkelanjutan.. Kata Kunci: Green Human Resource Management; Employee Green Behavior; Environmental Performance; Sustainability; Literature Review.